Vascular Wall-Resident Multipotent Stem Cells of Mesenchymal Nature within the Process of Vascular Remodeling: Cellular Basis, Clinical Relevance, and Implications for Stem Cell Therapy - Diana Klein (Stem Cells International)
Until some years ago, the bone marrow and the endothelial cell compartment lining the vessel lumen (subendothelial space) were thought to be the only sources providing vascular progenitor cells. Now, the vessel wall, in particular, the vascular adventitia, has been established as a niche for different types of stem and progenitor cells with the capacity to differentiate into both vascular and nonvascular cells. Herein, vascular wall-resident multipotent stem cells of mesenchymal nature (VW-MPSCs) have gained importance because of their large range of differentiation in combination with their distribution throughout the postnatal organism which is related to their existence in the adventitial niche, respectively. In general, mesenchymal stem cells, also designated as mesenchymal stromal cells (MSCs), contribute to the maintenance of organ integrity by their ability to replace defunct cells or secrete cytokines locally and thus support repair and healing processes of the affected tissues. This review will focus on the central role of VW-MPSCs within vascular reconstructing processes (vascular remodeling) which are absolute prerequisite to preserve the sensitive relationship between resilience and stability of the vessel wall. Further, a particular advantage for the therapeutic application of VW-MPSCs for improving vascular function or preventing vascular damage will be discussed.